Virological response and retention in care according to time of starting ART in Italy: data from the Icona Foundation Study cohort. (22nd December 2019) - d'Arminio Monforte, Antonella; Tavelli, Alessandro; Cozzi-Lepri, Alessandro; Castagna, Antonella; Passerini, Simone; Francisci, Daniela; Saracino, Annalisa; Maggiolo, Franco; Lapadula, Giuseppe; Girardi, Enrico; Perno, Carlo Federico; Antinori, Andrea; et al.
Abstract: Objectives: To describe: (i) factors associated with rapid and delayed ART initiation; (ii) rates of 12 week virological response; and (iii) virologically controlled retention in care by 1 year from ART initiation according to timing of start in a real-life setting. Methods: All individuals in the Icona cohort diagnosed with HIV in 2016–17 who initiated ART were grouped according to the time between HIV diagnosis and ART initiation: Group 1, ≤7 days; Group 2, 8–14 days; Group 3, 15–30 days; Group 4, 31–120 days; and Group 5, >120 days. Multivariable logistic regression models were used to identify factors associated with: (i) the probability of rapid (Group 1) and very delayed (Group 5) ART initiation; (ii) the 12 week virological response (by a modified snapshot algorithm); and (iii) the probability of retention in care at 1 year (on ART with HIV-RNA <50 copies/mL). Results: A total of 1247 individuals were included [82 (6.6%) in Group 1, 115 (9.2%) in Group 2, 267 (21.4%) in Group 3, 641 (51.4%) in Group 4 and 142 (11.4%) in Group 5]. Main predictors of rapid ART start (Group 1) were low CD4 cell count and high HIV-RNA at first contact with the infectious diseases centre. There was no association between probability of virological response and timing of ART initiation. Overall, 90% of individuals remained on ART after 1 year, 91% with undetectable HIV-RNA. Participants of Italian nationality, those with higher CD4 cell count and lower HIV-RNA at ART initiation were more likely to be retained in care after 1 year. Conclusions: In our high-income observational setting, we did not observe differences in the 1 year rate of virological response and retention in care according to timing of ART initiation.